(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2016)
This article analyses the financial rights of divorced Muslim women in three southern provinces of Thailand implemented through the Regional Islamic Religious Council and the Islamic religious courts in Pattani, Yala, Narathiwat and Satul according to the Application of Islamic Law Act, 1946. This study also examines the extent to which Muslim women here know their rights after divorce regarding mutaah (monetary gift), nafkah iddah (maintenance after divorce), mahar (dower) dan hadanah (child custody) which require proof. The provisions of this act are similar to those of the laws in Malaysia. The study found that there were few claims submitted by women in southern Thailand due to a lack of legal awareness on their financial rights after divorce and suggests that more efforts should be made to educate Muslim women about their financial rights after divorce. Keywords: Regional Islamic Religious Council, kadi courts, financial rights, Muslim women, souuthern Thailand